Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1002/ece3.3408
|View full text |Cite
|
Sign up to set email alerts
|

Limited polymorphism of the functional MHC class II B gene in the black‐spotted frog (Pelophylax nigromaculatus) identified by locus‐specific genotyping

Abstract: Amphibians can be more vulnerable to environmental changes and diseases than other species because of their complex life cycle and physiological requirements. Therefore, understanding the adaptation of amphibians to environmental changes is crucial for their conservation. Major histocompatibility complex (MHC) presents an excellent tool for the investigation of adaptive variations and the assessment of adaptive potential because it can be under strong diversifying selection. Here, we isolated the MHC class II … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…The other species included for MHC-II supertyping were: (a) B. orientalis and B. gargarizans (resistant) from South Korea [ 16 ]; (b) L. catesbeiana (transcriptome data, DRA accession number SRP051787); (c) L. yavapaiensis from North America [ 18 ]; (d) Z. omeimontis from China [ 45 ]; (e) representative sequences from Epidalea calamita (low susceptibility), Nanorana parkeri (susceptibility unclear), Rhinella marina (tolerant), and Quasipaa spinosa (susceptibility unclear) available in GenBank; and (f) L. verreauxii alpina (susceptible) from Australia but with some resistant populations or individuals [ 16 ]. MHC-IIb sequences from Chinese populations of P. nigromaculatus [ 46 ] were initially included but formed a very distinct ST cluster and thereby excluded.…”
Section: Methodsmentioning
confidence: 99%
“…The other species included for MHC-II supertyping were: (a) B. orientalis and B. gargarizans (resistant) from South Korea [ 16 ]; (b) L. catesbeiana (transcriptome data, DRA accession number SRP051787); (c) L. yavapaiensis from North America [ 18 ]; (d) Z. omeimontis from China [ 45 ]; (e) representative sequences from Epidalea calamita (low susceptibility), Nanorana parkeri (susceptibility unclear), Rhinella marina (tolerant), and Quasipaa spinosa (susceptibility unclear) available in GenBank; and (f) L. verreauxii alpina (susceptible) from Australia but with some resistant populations or individuals [ 16 ]. MHC-IIb sequences from Chinese populations of P. nigromaculatus [ 46 ] were initially included but formed a very distinct ST cluster and thereby excluded.…”
Section: Methodsmentioning
confidence: 99%
“…The heterozygote advantage hypothesis suggests that heterozygous genotypes have a higher relative fitness than homozygous genotypes. The diversity mechanism of MHC is a classic example of heterozygote advantage selection, as MHC heterozygous genotypes can potentially provide resistance to a wider range of antigens [ 9 , 10 ]. Many studies have found direct evidence for MHC-based mate choice [ 4 , 6 , 11 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%